PEMETAAN UKM (USAHA KECIL MENENGAH) BERBASIS AGRIBISNIS DI KECAMATAN MARTAPURA KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2016)
Mapping of SME (Small Medium Enterprise) Based Agribusiness in the District Martapura East Ulu Ogan Ogan. The purpose of this study is (1) Formulate mapping SME agribusiness in the District Martapura OKU Regency East and calculate the percentage of the existing cluster. (2) Analyzing the average difference in reception between clusters of SMEs based agribusiness in the District Martapura Timur.Penelitian OKU District have been carried out in the district of Ulu Ogan Ogan Martapura East. The location determination is done deliberately (purpusive) with the consideration that the population in East Ulu Ogan Ogan has many industry players household-based agribusiness. The results showed that (1) the District Martapura Ogan Ogan Ulu Timur has four (4) types of SMEs based agribusiness that SMEs Based Foods Agribusiness consisting of SMEs Bread, SME Soy Milk, SMEs Tempe, SMEs Know, SMEs Pecel, SMEs Meatballs , SMEs Chicken Noodle, and SMEs gado-gado, SME Furniture Based Agribusiness consists of SME Chair made from palm stems, SMEs Tables made of wood rattan, and SME Wardrobe, SMEs Crafts Based Agribusiness consists of SMEs fan made of corn and SMEs mats made of bamboo, SMEs tools Agribusiness Based Farming System consists of SMEs Hoe, Sickle SMEs, SMEs Spades, and SMEs Parang. (2) Based on the survey results revealed that the results of different test average overall acceptance of SMEs are as follows: SME food is Rp. 8,038,217, - per month, or 16.22 percent, the SME furniture is Rp. 20,366,666.67, - per month, or 41.10 percent, SME handicraft is Rp. 9.136 million, - per month, or 18.43 percent, SMEs farming tools, namely Rp. 12.009 million, - per month, or 24.23 percent of total revenue.